75 GBd InP‐HBT MUX‐DAC module for high‐symbol‐rate optical transmission. Issue 9 (1st April 2015) - Nagatani, M.; Wakita, H.; Nosaka, H.; Kurishima, K.; Ida, M.; Sano, A.; Miyamoto, Y.
Abstract : An ultra‐broadband 6 bit digital‐to‐analogue converter (DAC) has been designed and fabricated in InP‐HBT technology. The DAC IC includes six 2:1 MUXs and thus operates with a half‐rate clock. The DAC module is equipped with 1 mm connectors for its analogue output to ensure broadband characteristics. The measured analogue output bandwidth (BW) is >40 GHz. Four‐level pulse amplitude modulation signals with clear eye openings were measured at symbol rates of up to 75 GBd. This MUX‐DAC module has the widest BW of any previously reported DACs and is suitable for high‐symbol‐rate optical transmitters.